1985
DOI: 10.1128/mcb.5.6.1449
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties of a highly purified v-rasH p21 protein overproduced in Escherichia coli and inhibition of its activities by a monoclonal antibody.

Abstract: The v-rasH oncogene of Harvey murine sarcoma virus encodes a 21,000-dalton p21 protein which has been expressed at a high level as a fusion protein in Escherichia coli. We have purified the p21 to over 90% in purity without the use of any detergent or protein denaturant. The purified p21 possesses full biochemical activities of GTP/GDP binding, autokinase, and GTPase. Scatchard analysis indicates a single class of binding sites with Kd values of 0.83 x 10-8 M for GTP and 1.0 x 10-8 M for GDP. The binding site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
1

Year Published

1987
1987
1997
1997

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 25 publications
6
49
1
Order By: Relevance
“…As shown in Table 1, our purified p21 shows a very high affinity for GDP and GTP (K',, = lOpM), which is more than three orders of magnitude stronger than reported for p21 purified using denaturing agents (Hattori et al, 1985;Sigal et al, 1986;Clanton et al, 1986;Feig and Cooper, 1988) and in good agreement with results reported by other authors using methods avoiding denaturing agents Neal et al, 1988). (NH,),SO, strongly increases the dissociation rate of p21 (Table2), as already observed by Satoh et al (1988).…”
Section: Ionic Environment and P21 -Guanine-nucleotide Interactionsupporting
confidence: 80%
“…As shown in Table 1, our purified p21 shows a very high affinity for GDP and GTP (K',, = lOpM), which is more than three orders of magnitude stronger than reported for p21 purified using denaturing agents (Hattori et al, 1985;Sigal et al, 1986;Clanton et al, 1986;Feig and Cooper, 1988) and in good agreement with results reported by other authors using methods avoiding denaturing agents Neal et al, 1988). (NH,),SO, strongly increases the dissociation rate of p21 (Table2), as already observed by Satoh et al (1988).…”
Section: Ionic Environment and P21 -Guanine-nucleotide Interactionsupporting
confidence: 80%
“…One report (23) claimed that Y13-259 did not interfere with either the GTP-binding or the GTPase activity of v-Ha-ras protein produced in E. coli. On the other hand, it has been claimed that the same antibody blocked [3H]GTP binding and autophosphorylation of v-Ha-ras p21 (12,18) severely hampered the nucleotide exchange reaction between p21-bound and exogenous guanine nucleotides, and decreased the intrinsic GTPase of c-Ha-ras (17,20). These discrepancies probably come from the fact that in one case the protein was not completely renatured (23).…”
Section: Discussionmentioning
confidence: 71%
“…The bgalactosidase cDNA was excised out from pSV-b-galactosidase (Promega) by HindIII ± ApaI digestion, and subcloned into the pRc-CMV vector (pRc-CMV-b-Gal). The c-Ha-Ras V12 cDNA was cut out from pMT-cHr-2 (provided by Dr S Hattori) (Hattori et al, 1985) by BglII digestion, and subcloned into pRc-CMV with a NotI linker (pRc-CMV-Ras V12 ). SRa456 -XenopusD(32 ± 51) -S218E/S222E-MAPKK (DNSESE, provided by Drs Y Gotoh and E Nishida) (Gotoh et al, 1995) was digested with BglII and the BglII sites in both ends were substituted by NotI sites.…”
Section: Plasmid Constructionmentioning
confidence: 99%